2016
DOI: 10.1242/dmm.027326
|View full text |Cite
|
Sign up to set email alerts
|

Microglia activation in a pediatric rabbit model of tuberculous meningitis

Abstract: Central nervous system (CNS) tuberculosis (TB) is the most severe form of extra-pulmonary TB and disproportionately affects young children where the developing brain has a unique host response. New Zealand white rabbits were infected with Mycobacterium tuberculosis via subarachnoid inoculation at postnatal day 4-8 and evaluated until 4-6 weeks post-infection. Control and infected rabbit kits were assessed for the development of neurological deficits, bacterial burden, and postmortem microbiologic and pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 63 publications
2
59
0
Order By: Relevance
“…The developmental stages of the brain in children makes them highly vulnerable to TBM. To understand the pathogenesis of TB during early brain development, a pediatric rabbit model of TBM was created (Tucker et al, 2016). In this model, 4-8 day old NZW rabbits were inoculated with Mtb into the subarachnoid space, and the animals were monitored for 35 days post-infection.…”
Section: The Rabbit As a Preclinical Model To Assess The Pathogenesismentioning
confidence: 99%
“…The developmental stages of the brain in children makes them highly vulnerable to TBM. To understand the pathogenesis of TB during early brain development, a pediatric rabbit model of TBM was created (Tucker et al, 2016). In this model, 4-8 day old NZW rabbits were inoculated with Mtb into the subarachnoid space, and the animals were monitored for 35 days post-infection.…”
Section: The Rabbit As a Preclinical Model To Assess The Pathogenesismentioning
confidence: 99%
“…Several in vivo models to study mycobacterial pathogenesis exist, such as rabbits, guinea pig, and mice (Be et al, 2012; Be, Klinkenberg, Bishai, Karakousis, & Jain, 2011; Skerry et al, 2013; Tsenova et al, 2005; Tucker et al, 2016; van Well et al, 2007; Zucchi et al, 2012). However, none of these models could demonstrate the course of events during mycobacterial trafficking across the BBB in a living host.…”
Section: Introductionmentioning
confidence: 99%
“…Several in vivo models to study mycobacterial pathogenesis exist, such as rabbits, guinea pig, and mice Be, Klinkenberg, Bishai, Karakousis, & Jain, 2011;Skerry et al, 2013;Tsenova et al, 2005;Tucker et al, 2016;van Well et al, 2007;Zucchi et al, 2012).…”
mentioning
confidence: 99%
“…For MDR-and XDR-TBM, both of which are particularly lethal forms of TBM, treatment options are limited and outcomes are nearly universally poor. We used our experimentally induced TBM model in young rabbits due to its ability to reproducibly reflect the heterogeneity of disease (exudative meningitis and tuberculomas) and neurologic deficits in TBM patients (12,34). In our rabbit study, we found that the concentrations of DLM were almost 5-fold higher in brain than plasma in rabbits with and without CNS TB, while CSF concentrations were low but above the average MIC of DLM against M. tuberculosis, and estimates of CSF/plasma ratios of free drug were generally Ͼ1.…”
Section: Discussionmentioning
confidence: 99%
“…M. tuberculosis H37Rv (from the S.K.J. laboratory) was prepared from frozen titrated stock as previously described (12,34). Female and male New Zealand White (NZW) rabbits (Oryctolagus cuniculus; Robinson Services Inc., NC) were anesthetized and injected with approximately 1.42 Ϯ 0.21 log 10 CFU for infected rabbits or with phosphate-buffered saline (PBS; Quality Biological, Inc., Gaithersburg, MD) for uninfected rabbits on postnatal day (PND) 5 or 6 using a 28-gauge insulin syringe (28-gauge, 1/2-in.…”
Section: Methodsmentioning
confidence: 99%